Impact of spliceosome mutations on RNA splicing in myelodysplasia: dysregulated genes/pathways and clinical associations - Pellagatti, Andrea; Radujković, Aleksandar; Horn, Patrick; Ho, Anthony Dick; Luft, Thomas (Blood, 2018)
Key Points. RNA-seq analysis of CD34+ cells identifies novel aberrantly spliced genes and dysregulated pathways in splicing factor mutant MDS.Aberrantly splice
Gesehen am 07.02.2020